Letter - Miller, Wright Watts
001-0163-001 38 St. Peter's Square, Hammersmith, W.6. 24th April, 1942 Mr. Ernest Bell, Transport House, Smith Square, S.W.1 Dear Mr. Bell, In confirmation of our telephone conversation today, the Catalan who spoke to me about the Trade Union needs of some of his compatriots was Mr. F. Verges, 25 Blenheim Road, N.W.8. He was a journalist in Catalonia, speaks very good English, and I think often acts as a mouthpiece for other Catalans. Yours sincerely, Wright Miller 292/946/1/163